IMRT technique application in vertebra L3 giant cell tumour – a case report - Łożyńska-Podhrebelna, Diana; Ziółkowska, Ewa; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2007)
Giant cell tumour is a rare locally malignant neoplasm of the bone, which is characterised by a high risk of recurrence. The main management is surgery and, in the case of a nonradical operation, radiotherapy. The aim of the paper is to present the case of a 38-year-old woman with a diagnosis of giant cell tumour localised in the 3 rd vertebral body. For this rare localisation both surgery and radiotherapy are at high risk of neurological complications due to the close neighbourhood of critical organs (the spinal cone and cauda equina). The treatment of the patient consisted of a nonradical operation and postoperative radiotherapy with a total dose of 54 Gy given in 27 fractions. In this case the intensity modulated radiotherapy (IMRT) technique seemed to be specially beneficial (a high dose gradient), enabling radiosensitive critical organs to be protected. After 3 months, in spite of the treatment, a recurrence was detected by CT and the patient was reoperated on. The reason for the local regrowth of the tumour might be insufficient stabilization of the irradiated region. The literature reports only a few cases of IMRT usage for paraspinal tumour treatment. Immobilization body frames were used for these patients. Thus this modern radiotherapy technique requires not only a doctor’s experience but also improvement of ways of its application in new organ localisations.